Neck Circumference and Cardio- Metabolic Syndrome - Kumar, Nagendran Vijaya (JCDR Research and Publications (P) Limited, 2014)
Background: Only few studies about neck circumference (NC) as a measure of cardio metabolic syndrome available from India. Study was conducted to establish an association between neck circumference and cardio metabolic syndrome. Material and Methods: Cross-sectional study was conducted in a tertiary care hospital in South India. NCEP: ATPIII 2001 guideline was used for diagnosis of Cardio-metabolic syndrome among subjects. Neck circumference was measured and it was correlated with Cardio-metabolic syndrome. Results: Mean neck circumference was found to be 36.5 cms. Cardio-metabolic syndrome was present in 272 participants, of which 100 were females and 172 males. Among females 82(82%) had neck circumference >34cms, 18(18%) had <34cms and among males 117(68%)had NC >37cms and 55(32%) had NC<37cms. All individual parameter of cardio metabolic risk factor, i.e., BMI, waist circumference, hip circumference, systolic blood pressure, diastolic blood pressure, FBS, HDL & TG except waist/hip ratio were correlating with abnormal neck circumference when compared with those with normal neck circumference. Conclusion: Neck circumference with metabolic syndrome correlated better among females than males. Men with NC >37 cm and women with NC >34 cm are more prone for cardio metabolic syndrome and require additional evaluation. Measurement of NC is a simple, time saving, and least invasive measurement tool.